Characterization of NontyphoidalSalmonellaIsolates from Asymptomatic Migrant Food Handlers in Peninsular Malaysia - Woh, Pei Yee; Thong, Kwai Lin; Behnke, Jerzy Marian; Lewis, John Watkin; Mohd Zain, Siti Nursheena (International Association for Food Protection, 2017)
Asymptomatic Salmonella carriers who work as food handlers pose food safety and public health risks, particularly during food preparation, and this has serious implications for the disease burden in society. Therefore, we conducted a study to determine the number of Salmonella carriers in a migrant cohort in several food establishments in three major cities in Peninsular Malaysia. Sociodemographic data and stool samples were collected and analyzed using standard methods of detection and isolation. Antimicrobial susceptibility tests of the positive samples were also performed. A total of 317 migrant food handlers, originating from South and Southeast Asian countries, were recruited voluntarily. Nine (2.8%) stool samples were confirmed to be Salmonella positive. PCR serotyping and pulsed-field gel electrophoresis identified four serotypes as Typhimurium (n = 3), Corvallis (n=2), Hadar (n=1), Agona (n=1) and two unknown serovars. Antimicrobial susceptibility tests revealed that all nine isolates were susceptible to amoxicillin-clavulanic acid, cefotaxime, ceftazidime, ceftriaxone, and gentamycin. However, seven isolates were found to be multidrug resistant to ampicillin, chloramphenicol, trimethoprim-sulfamethoxazole, sulfonamides, streptomycin, and tetracycline. This study highlights that carriers of nontyphoidal Salmonella exist among migrant food handlers, which poses a health risk to consumers through food contamination. Our results indicate a need for authorities to enhance food safety awareness in the migrant workers and to reevaluate current health screening methods to include preventive measure such as mandatory stool screening as part of the preemployment and routine health examinations.